PKM2-c-Myc-Survivin Cascade Regulates the Cell Proliferation, Migration, and Tamoxifen Resistance in Breast Cancer - Pian Yu; Pian Yu; Ao-xue Li; Ao-xue Li; Xi-sha Chen; Xi-sha Chen; Min Tian; Min Tian; Hai-yan Wang; Xin-luan Wang; Yi Zhang; Kuan-song Wang; et al. (Frontiers Media S.A., 2020)
The M2 isoform of pyruvate kinase (PKM2), as a key glycolytic enzyme, plays important roles in tumorigenesis and chemotherapeutic drug resistance. However, the intricate mechanism of PKM2 as a protein kinase regulating breast cancer progression and tamoxifen resistance needs to be further clarified. Here, we reported that PKM2 controls the expression of survivin by phosphorylating c-Myc at Ser-62. Functionally, PKM2 knockdown suppressed breast cancer cell proliferation and migration, which could be rescued by overexpression of survivin. Interestingly, we found that the level of PKM2 expression was upregulated in the tamoxifen resistant breast cancer cells MCF-7/TAMR, and knockdown of PKM2 sensitized the cells to 4-hydroxytamoxifen (4OH-T). In addition, the elevated level of PKM2 correlates with poor relapse-free survival in breast cancer patients treated with tamoxifen. Overall, our findings demonstrated that PKM2-c-Myc-survivin cascade regulated the proliferation, migration and tamoxifen resistance of breast cancer cells, suggesting that PKM2 represents a novel prognostic marker and an attractive target for breast cancer therapeutics, and that PKM2 inhibitor combined with tamoxifen may be a promising strategy to reverse tamoxifen resistance in breast cancer patients.